ACEI in diabetes prevention – DREAM study commentary - Grzeszczak, Władysław (Przewodnik Lekarza/Guide for GPs, 2007)
Diabetes mellitus, as the main cause of death, is an important risk factor for cardiovascular complications and renal disease. Most antihypertensive drugs also indirectly affect carbohydrate metabolism. Examples of drugs reducing the incidence of diabetes mellitus include drugs that inhibit the RAA system. In the recently completed DREAM study, no significant reduction of risk for diabetes or all-cause mortality has been found in the group of patients treated with ramipril 15 mg. No reduction in the combined incidence of cardiovascular events has been found either. While the DREAM study, in the light of the previously completed HOPE study, has been a disappointment, it has not undermined the results of previous ACEI studies. The study remains another voice in the discussion about the absence of the class effect of ACEIs and the presence of differences between drugs.